High performance polymer compositions containing carbon nanostructures

JP2025504820APending Publication Date: 2025-02-19TICONA LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024541988
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-05
Filing Date
2023-01-06
Publication Date
2025-02-19

Smart Images

  • Figure 2025504820000001_ABST
    Figure 2025504820000001_ABST
Patent Text Reader

Abstract

A polymeric composition is provided that includes carbon nanostructures dispersed within a polymer matrix that includes a thermoplastic polymer having a deflection temperature under load of about 40° C. or greater and a melting temperature of about 140° C. or greater, as determined according to ISO 75:2013 at a load of 1.8 MPa. The carbon nanostructures include carbon nanotubes arranged in a network having a mesh-like morphology, optionally disposed on a substrate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Related Applications

[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 299,122, filed January 13, 2022, and U.S. Provisional Patent Application No. 63 / 327,442, filed April 5, 2022, which are incorporated by reference in their entireties herein. [Background technology]

[0002] Electronic components (e.g., printed circuit boards, antenna elements, radio frequency devices, sensors, light sensing and / or transmitting elements (e.g., optical fibers), camera modules, global positioning devices, etc.) typically contain polymeric materials for a variety of different purposes. In some cases, it is desirable for these compositions to have some degree of electrical conductivity. For example, radar devices typically include one or more printed circuit boards with dedicated electrical components for handling radio frequency (RF) radar signals, digital signal processing tasks, etc. To ensure that these components operate effectively at high frequencies, they are typically housed within a housing structure and covered with a radio wave transparent radome. Because other surrounding electrical devices can generate electromagnetic interference ("EMI") that can affect the correct operation of the radar device, it is often desirable to use polymeric materials in radar devices that have a sufficient degree of electrical conductivity to provide EMI shielding. Similarly, camera modules are often used in mobile phones, laptop computers, digital cameras, digital video cameras, etc. It is often desirable to use polymeric materials in camera modules that have a sufficient degree of electrical conductivity to provide electrostatic discharge, since friction between molded parts can induce electrostatic charging if not handled properly, which can lead to the formation of dust particles (e.g., during transportation). Various electrically conductive polymeric materials have been attempted for use in these applications, but it is often difficult to achieve the desired degree of electrical conductivity without adversely affecting other properties of the composition, especially when high performance polymers are used. Summary of the Invention [Problem to be solved by the invention]

[0003]

[0003] Thus, there is currently a need for improved high performance polymer compositions which are capable of exhibiting some degree of electrical conductivity. [Means for solving the problem]

[0004] According to one embodiment of the present invention, a polymer composition is disclosed that includes carbon nanostructures dispersed within a polymer matrix that includes a thermoplastic polymer having a deflection temperature under load of about 40° C. or more and a melting temperature of about 140° C. or more, as determined at a load of 1.8 MPa according to ISO 75:2013. The carbon nanostructures include carbon nanotubes arranged in a network having a mesh-like morphology and optionally disposed on a substrate.

[0005]

[0005] Other features and aspects of the present invention are described in more detail below.

[0006] A full and enabling disclosure of the present invention, including the best mode thereof to one skilled in the art, is set forth more particularly in the remainder of the specification, including reference to the accompanying figures. [Brief description of the drawings]

[0006] [Figure 1]

[0007] Figure 1A shows an illustrative depiction of an embodiment of a carbon nanotube that may be used in the present invention. Figure 1B shows an illustrative depiction of an embodiment of a carbon nanotube that may be used in the present invention. Figure 1C shows an illustrative depiction of an embodiment of a carbon nanotube that may be used in the present invention. [Diagram 2]

[0008] FIG. 2 shows an illustrative depiction of carbon nanostructure flake materials that may be used in the polymer compositions of the present invention. [Diagram 3]

[0009] FIG. 3 shows an SEM image of illustrative carbon nanostructures that may be used in the polymer compositions of the present invention. [Figure 4]

[0010] FIG. 4 is a schematic exploded perspective view of a radar device in which the polymer composition of the present invention may be used. [Diagram 5]

[0011] FIG. 5 is a perspective view of a camera module that may be formed in accordance with one embodiment of the present invention. [Figure 6]

[0012] FIG. 6 is a top perspective view of one embodiment of an electronic device including a camera module of the present invention. [Figure 7]

[0013] FIG. 7 is a bottom perspective view of the electronic device shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007]

[0014] Those skilled in the art should understand that this discussion is a description of exemplary embodiments only, and is not intended to limit the broader aspects of the invention.

[0015] Generally speaking, the present invention is directed to a polymer composition containing carbon nanostructures dispersed within a polymer matrix comprising a thermoplastic polymer having a deflection temperature under load of about 40° C. or more, as determined at a load of 1.8 MPa according to ISO 75:2013, and a melting temperature of about 140° C. or more. The carbon nanostructures include carbon nanotubes, optionally disposed on a substrate, arranged in a network having a mesh-like morphology. It has been discovered that by selectively controlling the specific components of the composition and their relative concentrations, the resulting composition can exhibit unique properties for use in a wide variety of potential product applications, such as electronic devices (e.g., radar equipment) and other applications requiring electrically conductive polymeric materials. The surface resistivity, as determined at a temperature of about 20° C. according to, for example, IEC 62631-3-2:2016, can be, for example, about 1×10 12 Ω or less, in some embodiments about 1×10 10 Ω or less, in some embodiments about 1×10 7 Ω or less, in some embodiments about 1×10 3 ~Approx. 1×10 6 The volume resistivity may also be about 1×10 Ω, determined at a temperature of about 20° C. according to, for example, IEC 62631-3-1:2016. 7 Ω·m or less, in some embodiments about 1×10 6 Ω·m or less, in some embodiments about 1×10 5 Ω·m or less, in some embodiments about 1×10 2~Approx. 1×10 4 It may be Ω·m.

[0008]

[0016] In certain embodiments, for example, the polymer composition may exhibit an EMI shielding effectiveness ("SE") of about 40 decibels (dB) or greater, in some embodiments about 45 dB or greater, in some embodiments about 50 dB or greater, and in some embodiments about 55 dB to about 200 dB, as determined at high frequencies, such as 6 GHz, according to ASTM D4935-18. The EMI shielding effectiveness may remain stable over a high frequency range, such as about 700 MHz or greater, in some embodiments about 1 GHz to about 100 GHz, and in some embodiments about 2 GHz to about 18 GHz. The EMI shielding effectiveness may also be within a desired range for a variety of different part thicknesses, such as about 0.5 to about 10 millimeters, in some embodiments about 0.8 to about 5 millimeters, and in some embodiments about 1 to about 4 millimeters (e.g., 1 millimeter, 1.6 millimeters, or 3 millimeters). Within these high frequency and / or thickness ranges, for example, the average EMI shielding effectiveness may be about 40 dB or more, in some embodiments about 45 dB or more, and in some embodiments about 50 dB to about 200 dB. Similarly, the minimum EMI shielding effectiveness may be about 10 dB or more, in some embodiments about 15 dB or more, and in some embodiments about 20 dB to about 100 dB. The composition may also have good EMI shielding effectiveness at low frequencies, such as 200 MHz to 1.5 GHz. For example, within these low frequency ranges and thickness ranges noted above, the average EMI shielding effectiveness may be about 50 dB or more, in some embodiments about 55 dB or more, and in some embodiments about 60 dB to about 200 dB.

[0009]

[0017] Traditionally, it has been believed that polymer compositions that exhibit good electrical conductivity and / or EMI shielding effectiveness also do not have sufficient mechanical properties to be used in certain types of devices. However, it has been discovered that the polymer compositions can still maintain excellent mechanical properties. For example, the polymer compositions have a mechanical conductivity of about 2 kJ / m2 as measured according to ISO Test No. 179-1:2010 (technically equivalent to ASTM D6110) at various temperatures, e.g., within a temperature range of about -50°C to about 85°C (e.g., at 23°C). 2 In some embodiments, about 4 to about 50 kJ / m 2 In some embodiments, from about 6 to about 30 kJ / m 2The polymer composition may exhibit a notched Charpy impact strength of about 50 MPa or more, in some embodiments about 80 MPa or more, and in some embodiments about 100 to about 200 MPa; a tensile strain at break of about 0.1% or more, in some embodiments about 0.5% to about 5%, and in some embodiments about 0.8% to about 2.5%; and / or a tensile modulus of about 5,000 MPa to about 50,000 MPa, in some embodiments about 10,000 MPa to about 40,000 MPa, and in some embodiments about 15,000 MPa to about 35,000 MPa. Tensile properties may be determined at various temperatures, for example, within a temperature range of about -50°C to about 85°C (e.g., 23°C), according to ISO Test No. 527-1:2019 (technically equivalent to ASTM D638-14). The polymeric composition may also exhibit a flexural strength of about 100 to about 600 MPa, in some embodiments about 120 to about 500 MPa, and in some embodiments about 150 to about 400 MPa; a flexural strain at break of about 0.5% or greater, in some embodiments about 0.8% to about 5%, and in some embodiments about 1.0% to about 2.5%; and / or a flexural modulus of about 5,000 MPa to about 60,000 MPa, in some embodiments about 10,000 MPa to about 55,000 MPa, and in some embodiments about 15,000 MPa to about 40,000 MPa. Flexural properties may be determined at various temperatures, for example, within a temperature range of about -50°C to about 85°C (e.g., 23°C), according to ISO Test No. 178:2019 (technically equivalent to ASTM D790-17).

[0010]

[0018] The composition may also have good thermal properties. For example, the polymeric composition may exhibit a temperature deflection under load (DTUL) of about 150° C. or more, in some embodiments about 200° C., and in some embodiments about 250° C. to about 300° C., as determined according to ISO 75:2013 (technically equivalent to ASTM D648-07) at a specified load of 1.8 MPa. The polymeric composition may also be thermally conductive, and thus may exhibit an in-plane thermal conductivity of, for example, about 1 W / m·K or more, in some embodiments about 1.5 W / m·K or more, and in some embodiments about 2 to about 10 W / m·K, as determined according to ASTM E1461-13. The composition may also exhibit a through thickness thermal conductivity of about 0.3 W / m·K or more, in some embodiments about 0.4 W / m·K or more, in some embodiments about 0.5 W / m·K or more, and in some embodiments about 0.7 to about 3 W / m·K, as determined according to ASTM E1461-13. The melt viscosity of the polymer composition is also measured in accordance with ISO 11443:2021 at 1,000 sec. -1 and at a temperature about 15° C. above the melting temperature of the polymer composition, may be very low, for example, from about 0.1 to about 150 Pa s, in some embodiments from about 0.2 to about 100 Pa s, in some embodiments from about 0.5 to about 80 Pa s, and in some embodiments, from about 1 to about 50 Pa s.

[0011]

[0019] Various embodiments of the invention will now be described in more detail. I. Polymer Matrix A. Thermoplastic polymers

[0020] As noted, the polymer matrix may contain one or more thermoplastic polymers. Typically, such polymers desirably have a high degree of heat resistance, as reflected by a deflection temperature under load ("DTUL") of about 40°C or more, in some embodiments about 50°C or more, in some embodiments about 60°C or more, in some embodiments about 80°C to about 250°C, and in some embodiments about 100°C to about 200°C, as determined at 1.8 MPa load according to ISO 75:2013. Thermoplastic polymers may also be semi-crystalline or crystalline in nature and exhibit high melting temperatures, such as about 140°C or more, in some embodiments about 150°C to about 400°C, and in some embodiments about 200°C to about 380°C. The melting temperature may be determined using differential scanning calorimetry ("DSC") according to ISO 11357-3:2018. Of course, in addition to exhibiting a high degree of heat resistance and a high melting temperature, the thermoplastic polymer may also exhibit a high glass transition temperature, such as about 10° C. or higher, in some embodiments about 20° C. or higher, in some embodiments about 30° C. or higher, in some embodiments about 40° C. or higher, in some embodiments about 50° C. or higher, and in some embodiments about 60° C. to about 320° C. The glass transition temperature may be determined using differential scanning calorimetry according to ISO 11357-2:2020.

[0012]

[0021] Suitable thermoplastic polymers for this purpose may include, for example, polyolefins (e.g., ethylene polymers, propylene polymers, etc.), polyamides (e.g., aliphatic, semi-aromatic or aromatic polyamides), polyesters, polyarylene sulfides, liquid crystal polymers (e.g., wholly aromatic polyesters, polyesteramides, etc.), polyethers (e.g., polyoxymethylene), polyaryletherketones, etc., as well as blends thereof. The exact selection of the polymer system will depend on a variety of factors, such as the nature of other fillers included within the composition, the manner in which the composition is formed and / or processed, and the particular requirements of the intended application.

[0013]

[0022] For example, aromatic polymers are particularly suitable in certain applications. One example of a suitable semi-crystalline aromatic polymer is, for example, an aromatic polyester, which may be a condensation product of at least one diol (e.g., aliphatic and / or cycloaliphatic), such as those having 4 to 20 carbon atoms, and in some embodiments 8 to 14 carbon atoms, with at least one aromatic dicarboxylic acid. Suitable diols include, for example, neopentyl glycol, cyclohexanedimethanol, 2,2-dimethyl-1,3-propanediol, and carboxylic acids of the formula HO(CH2). n OH, where n is an integer from 2 to 10. Suitable aromatic dicarboxylic acids may include, for example, isophthalic acid, terephthalic acid, 1,2-di(p-carboxyphenyl)ethane, 4,4'-dicarboxydiphenyl ether, and the like, as well as combinations thereof. Fused rings may also be present, for example, in 1,4- or 1,5- or 2,6-naphthalene-dicarboxylic acids. Specific examples of such aromatic polyesters may include, for example, poly(ethylene terephthalate) (PET), poly(1,4-butylene terephthalate) (PBT), poly(1,3-propylene terephthalate) (PPT), poly(1,4-butylene 2,6-naphthalate) (PBN), poly(ethylene 2,6-naphthalate) (PEN), poly(1,4-cyclohexylene dimethylene terephthalate) (PCT), as well as mixtures of the foregoing.

[0014]

[0023] Derivatives and / or copolymers of aromatic polyesters (e.g., polyethylene terephthalate) may also be used. In one embodiment, for example, modifying acids and / or modifying diols may be used to form derivatives of such polymers. As used herein, the terms "modifying acid" and "modifying diol" are intended to define compounds that can form part of the acid and diol repeat units of a polyester, respectively, and that can modify the polyester to reduce its crystallinity. Examples of modifying acid components include, but are not limited to, isophthalic acid, phthalic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2,6-naphthaline dicarboxylic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, suberic acid, 1,12-dodecanedioic acid, and the like. In practice, it is often preferred to use functional acid derivatives thereof, such as the dimethyl, diethyl, or dipropyl esters of the dicarboxylic acids. Anhydrides or acid halides of these acids may also be used where practical. Examples of the diol component to be modified include neopentyl glycol, 1,4-cyclohexanedimethanol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, Z,8-bis(hydroxymethyltricyclo-[5.2.1.0]-decane, [wherein Z represents 3, 4 or 5]; may include, but are not limited to, 1,4-bis(2-hydroxyethoxy)benzene, 4,4'-bis(2-hydroxyethoxydiphenyl ether [bis-hydroxy-ethyl bisphenol A], 4,4'-bis(2-hydroxyethoxy)diphenyl sulfide [bis-hydroxy-ethyl bisphenol S] and diols containing one or more oxygen atoms in the chain, such as diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, and the like.Generally, these diols contain from 2 to 18 carbon atoms, and in some embodiments, from 2 to 8 carbon atoms. The alicyclic diols can be used in their cis or trans configuration, or as a mixture of both forms.

[0015]

[0024] For example, the aromatic polyesters described above typically have a DTUL value of about 40°C to about 80°C, about 45°C to about 75°C in some embodiments, and about 50°C to about 70°C in some embodiments, as determined at a load of 1.8 MPa according to ISO 75:2013. The aromatic polyesters also typically have a glass transition temperature of about 30°C to about 120°C, about 40°C to about 110°C in some embodiments, and about 50°C to about 100°C in some embodiments, as well as a melting temperature of about 170°C to about 300°C, about 190°C to about 280°C in some embodiments, and about 210°C to about 260°C in some embodiments. The aromatic polyesters may also have an intrinsic viscosity of about 0.1 dl / g to about 6 dl / g, about 0.2 to about 5 dl / g in some embodiments, and about 0.3 to about 1 dl / g in some embodiments, as determined, for example, according to ISO 1628-5:1998.

[0016]

[0025] Polyarylene sulfide is also a suitable semi-crystalline aromatic polymer. Polyarylene sulfide may be a homopolymer or a copolymer. For example, the selective combination of dihaloaromatic compounds can result in a polyarylene sulfide copolymer containing at least two different units. For example, when p-dichlorobenzene is used in combination with m-dichlorobenzene or 4,4'-dichlorodiphenyl sulfone, a polyarylene sulfide copolymer containing a segment having the structure of the following formula can be formed:

[0017] [ka]

[0018] and a segment having the structure:

[0019] [ka]

[0020] or a segment having the structure:

[0021] [ka]

[0022]

[0026] Polyarylene sulfides may be linear, semi-linear, branched or crosslinked. Linear polyarylene sulfides usually contain 80 mol % or more of the repeating unit -(Ar-S)-. Such linear polymers may also contain a small amount of branching or crosslinking units, but the amount of branching or crosslinking units is usually less than about 1 mol % of the total monomer units of the polyarylene sulfide. Linear polyarylene sulfide polymers may be random or block copolymers containing the aforementioned repeating units. Semi-linear polyarylene sulfides may also have a crosslinked or branched structure in which a small amount of one or more monomers having three or more reactive functional groups are introduced into the polymer. As an example, the monomeric components used to form semi-linear polyarylene sulfides may include an amount of polyhaloaromatic compounds having two or more halogen substituents per molecule that can be utilized in preparing branched polymers. Such monomers are represented by the formula R'X nwhere each X is selected from chlorine, bromine, and iodine, n is an integer from 3 to 6, and R' is a polyvalent aromatic radical of valence n which may have up to about four methyl substituents, and the total number of carbon atoms in R' is in the range of 6 to about 16. Examples of some polyhaloaromatic compounds having more than two substituted halogens per molecule that can be used to form semi-linear polyarylene sulfides include 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, 1,3-dichloro-5-bromobenzene, 1,2,4-triiodobenzene, 1,2,3,5-tetrabromobenzene, hexachlorobenzene, 1,3,5-trichloro-2,4,6-trimethylbenzene, 2,2',4,4'-tetrachlorobiphenyl, 2,2',5,5'-tetra-iodobiphenyl, 2,2',6,6'-tetrabromo-3,3',5,5'-tetramethylbiphenyl, 1,2,3,4-tetrachloronaphthalene, 1,2,4-tribromo-6-methylnaphthalene, and the like, and mixtures thereof.

[0023]

[0027] For example, the polyarylene sulfide typically has a DTUL value of about 70° C. to about 220° C., about 90° C. to about 200° C. in some embodiments, and about 120° C. to about 180° C. in some embodiments, as determined under a load of 1.8 MPa according to ISO 75:2013. Similarly, the polyarylene sulfide typically has a glass transition temperature of about 50° C. to about 120° C., about 60° C. to about 115° C. in some embodiments, and about 70° C. to about 110° C. in some embodiments, and a melting temperature of about 220° C. to about 340° C., about 240° C. to about 320° C. in some embodiments, and about 260° C. to about 300° C. in some embodiments.

[0024]

[0028] Another suitable semi-crystalline aromatic polymer that may be used in the present invention is polyaryletherketone. Polyaryletherketone is a semi-crystalline polymer having a relatively high melting temperature, such as from about 300°C to about 400°C, in some embodiments from about 310°C to about 390°C, and in some embodiments from about 330°C to about 380°C. The glass transition temperature may also be from about 110°C to about 200°C. Particularly suitable polyaryletherketones are those that contain primarily phenyl moieties linked with ketone and / or ether moieties. Examples of such polymers include polyetheretherketone ("PEEK"), polyetherketone ("PEK"), polyetherketoneketone ("PEKK"), polyetherketoneetherketoneketone ("PEKEKK"), polyetheretherketoneketone ("PEEKK"), polyether-diphenylether-ether-diphenylether-phenylketone-phenyl, and the like, as well as blends and copolymers thereof.

[0025]

[0029] In addition to the polymers referenced above, highly crystalline aromatic polymers may also be used in the polymer composition. Particularly suitable examples of such polymers are liquid crystal polymers, which have a high degree of crystallinity that allows them to effectively fill small spaces in the mold. Polymers are generally classified as "thermotropic" to the extent that they have a rod-like structure and can exhibit crystalline behavior in the molten state (e.g., a thermotropic nematic state). Such polymers typically have a DTUL value of about 120°C to about 340°C, in some embodiments about 140°C to about 320°C, and in some embodiments about 150°C to about 300°C, as determined at 1.8 MPa according to ISO 75:2013. The polymers also have relatively high melting temperatures, such as about 250°C to about 400°C, in some embodiments about 280°C to about 390°C, and in some embodiments about 300°C to about 380°C. As is known in the art, such polymers may be formed from one or more types of repeating units.

[0026]

[0030] The liquid crystal polymer may, for example, typically comprise one or more aromatic ester repeat units in an amount of about 60 mol % to about 100 mol %, in some embodiments about 70 mol % to about 99.5 mol %, and in some embodiments about 80 mol % to about 99 mol % of the polymer. The aromatic ester repeat unit may generally be represented by the following formula (V):

[0027] [ka]

[0028] [In the formula, Ring B is a substituted or unsubstituted six-membered aryl group (e.g., 1,4-phenylene or 1,3-phenylene), a substituted or unsubstituted six-membered aryl group fused to a substituted or unsubstituted five- or six-membered aryl group (e.g., 2,6-naphthalene), or a substituted or unsubstituted six-membered aryl group linked to a substituted or unsubstituted five- or six-membered aryl group (e.g., 4,4-biphenylene); Y 1 and Y 2 are independently O, C(O), NH, C(O)HN or NHC(O).

[0029]

[0031] Usually, Y 1 and Y 2 At least one of Y is C(O). Examples of such aromatic ester repeating units include aromatic dicarboxylic acid repeating units (in formula V, Y 1 and Y 2 is C(O)), aromatic hydroxycarboxylic acid repeating units (Y in formula V 1 is O and Y 2 is C(O).) as well as various combinations thereof.

[0030]

[0032] For example, aromatic dicarboxylic acid repeat units derived from aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, diphenylether-4,4'-dicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, bis(4-carboxyphenyl)ether, bis(4-carboxyphenyl)butane, bis(4-carboxyphenyl)ethane, bis(3-carboxyphenyl)ether, bis(3-carboxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may be used. Particularly suitable aromatic dicarboxylic acids may include, for example, terephthalic acid ("TA"), isophthalic acid ("IA"), and 2,6-naphthalenedicarboxylic acid ("NDA"). When used, repeat units derived from aromatic dicarboxylic acids (e.g., IA, TA and / or NDA) typically comprise from about 5 mol % to about 60 mol %, in some embodiments from about 10 mol % to about 50 mol %, and in some embodiments, from about 20 mol % to about 40 mol % of the polymer.

[0031]

[0033] Aromatic hydroxycarboxyl repeat units derived from aromatic hydroxycarboxylic acids, such as 4-hydroxybenzoic acid; 4-hydroxy-4'-biphenylcarboxylic acid; 2-hydroxy-6-naphthoic acid; 2-hydroxy-5-naphthoic acid; 3-hydroxy-2-naphthoic acid; 2-hydroxy-3-naphthoic acid; 4'-hydroxyphenyl-4-benzoic acid; 3'-hydroxyphenyl-4-benzoic acid; 4'-hydroxyphenyl-3-benzoic acid, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may also be used. Particularly suitable aromatic hydroxycarboxylic acids are 4-hydroxybenzoic acid ("HBA") and 6-hydroxy-2-naphthoic acid ("HNA"). When used, repeat units derived from hydroxycarboxylic acids (e.g., HBA and / or HNA) typically comprise from about 10 mol% to about 75 mol%, in some embodiments from about 20 mol% to about 60 mol%, and in some embodiments from about 30 mol% to about 50 mol% of the polymer.

[0032]

[0034] Other repeat units may also be used in the polymer. In some embodiments, repeat units derived from aromatic diols, such as hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl (or 4,4'-biphenol), 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, bis(4-hydroxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may be used. Particularly suitable aromatic diols may include, for example, hydroquinone ("HQ") and 4,4'-biphenol ("BP"). When used, repeat units derived from aromatic diols (e.g., HQ and / or BP) typically comprise from about 1 mol % to about 50 mol %, in some embodiments from about 5 mol % to about 45 mol %, and in some embodiments from about 10 mol % to about 40 mol % of the polymer. Repeat units, such as those derived from aromatic amides (e.g., acetaminophen ("APAP")) and / or aromatic amines (e.g., 4-aminophenol ("AP")), 3-aminophenol, 1,4-phenylenediamine, 1,3-phenylenediamine, and the like, may also be used. When used, repeat units derived from aromatic amides (e.g., APAP) and / or aromatic amines (e.g., AP) typically comprise from about 0.1 mol % to about 20 mol %, in some embodiments from about 0.5 mol % to about 15 mol %, and in some embodiments from about 1 mol % to about 10 mol % of the polymer. It should also be understood that repeat units of various other monomers may be incorporated into the polymer. For example, in certain embodiments, the polymer may include one or more repeat units derived from non-aromatic monomers, such as aliphatic or alicyclic hydroxycarboxylic acids, dicarboxylic acids, diols, amides, amines, and the like. Of course, in other embodiments, the polymer may be "fully aromatic," in that there are no repeat units derived from non-aromatic (e.g., aliphatic or alicyclic) monomers.

[0033]

[0035] In a particular embodiment, the liquid crystal polymer may be a "high naphthene" polymer insofar as it contains a relatively high content of repeat units derived from naphthenic hydroxycarboxylic acids and naphthenic dicarboxylic acids, such as NDA, HNA, or a combination thereof. That is, the total amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids (e.g., NDA, HNA, or a combination of HNA and NDA) is typically about 10 mol% or more of the polymer, in some embodiments about 12 mol% or more, in some embodiments about 15 mol% or more, and in some embodiments about 18 mol% to about 35 mol%. In one embodiment, for example, the repeat units derived from NDA may constitute 10 mol% or more of the polymer, in some embodiments about 12 mol% or more, in some embodiments about 15 mol% or more, and in some embodiments about 18 mol% to about 35 mol%. When employed, the molar ratio of repeat units derived from HBA to repeat units derived from naphthenic units (e.g., NDA, HNA, or both) may be selectively controlled within a particular range, for example, from about 1 to about 20, in some embodiments from about 1.5 to about 15, in some embodiments from about 2 to about 10, to help achieve desired properties. The polymer may also contain repeat units derived from aromatic dicarboxylic acid(s) (e.g., IA and / or TA) in an amount of from about 1 mol % to about 20 mol %, in some embodiments from about 2 mol % to about 15 mol %; and / or aromatic diol(s) (e.g., BP and / or HQ) in an amount of from about 20 mol % to about 50 mol %, in some embodiments from about 30 mol % to about 45 mol %. However, in some cases, it may be desirable to minimize the presence of such monomers in the polymer to help achieve desired properties. For example, the total amount of repeat units derived from aromatic dicarboxylic acid(s) (e.g., IA and / or TA), and / or aromatic diol (e.g., BP and / or HQ) may be up to about 5 mol %, in some embodiments up to about 4 mol %, and in some embodiments, from about 0.1 mol % to about 3 mol % of the polymer.

[0034]

[0036] In some embodiments, the liquid crystal polymers are all "high naphthene" polymers as described above. However, in other embodiments, "low naphthene" liquid crystal polymers may also be used in compositions in which the total amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids (e.g., NDA, HNA, or a combination of HNA and NDA) is less than 10 mol %, in some embodiments about 8 mol % or less, in some embodiments about 6 mol % or less, and in some embodiments about 1 mol % to about 5 mol % of the polymer. When used, it is generally desirable that such low naphthene polymers are present in relatively small amounts. For example, when used, low naphthene liquid crystal polymers typically comprise about 1 wt % to about 50 wt %, in some embodiments about 10 wt % to about 45 wt %, in some embodiments about 15 wt % to about 40 wt %, of the total amount of liquid crystal polymer in the composition, and about 0.5 wt % to about 45 wt %, in some embodiments about 2 wt % to about 35 wt %, and in some embodiments about 5 wt % to about 25 wt % of the total composition. Conversely, the high naphthenic liquid crystalline polymer typically comprises from about 50% to about 99% by weight, in some embodiments from about 55% to about 95% by weight, and in some embodiments from about 60% to about 85% by weight of the total amount of liquid crystalline polymer in the composition, from about 25% to about 65% by weight, in some embodiments from about 30% to about 60% by weight, and in some embodiments from about 35% to about 55% by weight of the total composition.

[0035]

[0037] Of course, besides aromatic polymers, aliphatic polymers may also be suitable for use as high-performance thermoplastic polymers in the polymer matrix. In one embodiment, for example, polyamides may be used, which generally have CO-NH linkages in the main chain and are obtained by condensation of aliphatic diamines with aliphatic dicarboxylic acids, by ring-opening polymerization of lactams, or by self-condensation of aminocarboxylic acids. For example, the polyamides may contain aliphatic repeat units derived from aliphatic diamines, usually having 4 to 14 carbon atoms. Examples of such diamines include straight chain aliphatic alkylenediamines such as 1,4-tetramethylenediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, etc.; branched aliphatic alkylenediamines such as 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 2,4-dimethyl-1,6-hexanediamine, 2-methyl-1,8-octanediamine, 5-methyl-1,9-nonanediamine, etc.; and combinations thereof. Aliphatic dicarboxylic acids may include, for example, adipic acid, sebacic acid, etc. Specific examples of such aliphatic polyamides include, for example, nylon-4 (poly-α-pyrrolidone), nylon-6 (polycaproamide), nylon-11 (polyundecaneamide), nylon-12 (polydodecanamide), nylon-46 (polytetramethylene adipamide), nylon-66 (polyhexamethylene adipamide), nylon-610, and nylon-612. Nylon-6 and nylon-66 are particularly suitable.

[0036]

[0038] It should also be understood that it is possible to include aromatic monomer units in the polyamide such that it is considered aromatic (containing only aromatic monomer units, or both aliphatic and aromatic monomer units). Examples of aromatic dicarboxylic acids may include, for example, terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,4-phenylenedioxydiacetic acid, 1,3-phenylenedioxydiacetic acid, diphenic acid, 4,4'-oxydibenzoic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, 4,4'-biphenyldicarboxylic acid, and the like.Particularly suitable aromatic polyamides are poly(nonamethylene terephthalamide) (PA9T), poly(nonamethylene terephthalamide / nonamethylene decanediamide) (PA9T / 910), poly(nonamethylene terephthalamide / nonamethylene dodecanediamide) (PA9T / 912), poly(nonamethylene terephthalamide / 11-amino undecane amide) (PA9T / 11), poly(nonamethylene terephthalamide / 12-amino dodecane amide) (PA9T / 12), poly(decamethylene terephthalamide / 11-amino undecane amide) (PA10T / 11), poly(decamethylene terephthalamide / 12-amino dodecane amide) (PA10T / 12), poly(decamethylene terephthalamide / 11-amino undecane amide) (PA10T / 11), poly(decamethylene terephthalamide / 12-amino dodecane amide) (PA10T / 12), poly(decamethylene terephthalamide / 11-amino undecane amide) (PA10T / 12), poly(decamethylene terephthalamide / 12-amino do ... poly(decamethylene terephthalamide / hexamethylene hexanediamide) (PA10T / 66), poly(dodecamethylene terephthalamide / dodecamethylene dodecanediamide) (PA10T / 1010), poly(decamethylene terephthalamide / decamethylene dodecanediamide) (PA10T / 1012), poly(decamethylene terephthalamide / tetramethylene hexanediamide) (PA10T / 46), poly(decamethylene terephthalamide / caprolactam) (PA10T / 6), poly(decamethylene terephthalamide / hexamethylene hexanediamide) (PA10T / 66), poly(dodecamethylene terephthalamide / dodecamethylene dodecanediamide) (PA10T / 66) Poly(dodecamethylene terephthalamide / hexamethylene hexanediamide) (PA12T / 66), poly(dodecamethylene terephthalamide / caprolactam) (PA12T / 1212), poly(dodecamethylene terephthalamide / caprolactam) (PA12T / 6), poly(dodecamethylene terephthalamide / hexamethylene hexanediamide) (PA12T / 66), and the like.

[0037]

[0039] Polyamides suitable for the polymer matrix are typically crystalline or semi-crystalline in nature and therefore have a measurable melting temperature. The melting temperature may be relatively high so that the composition can impart a significant degree of heat resistance to the resulting part. For example, the polyamide may have a melting temperature of about 220°C or higher, in some embodiments from about 240°C to about 325°C, and in some embodiments from about 250°C to about 335°C. The polyamide may also have a relatively high glass transition temperature, such as about 30°C or higher, in some embodiments from about 40°C or higher, and in some embodiments from about 45°C to about 140°C.

[0038]

[0040] Propylene polymers may also be suitable aliphatic high performance polymers used in the polymer matrix. In general, any of a variety of propylene polymers or combinations of propylene polymers may be used in the polymer matrix, such as, for example, propylene homopolymers (e.g., syndiotactic, atactic, isotactic, etc.), propylene copolymers, etc. In one embodiment, a propylene polymer may be used that is, for example, an isotactic or syndiotactic homopolymer. In general, the term "syndiotactic" refers to a tacticity in which a significant portion (if not all) of the methyl groups are alternately on opposite sides along the polymer chain. On the other hand, the term "isotactic" generally refers to a tacticity in which a significant portion (if not all) of the methyl groups are on the same side along the polymer chain. In yet other embodiments, copolymers of propylene with α-olefin monomers may be used. Specific examples of suitable α-olefin monomers may include ethylene, 1-butene, 3-methyl-1-butene, 3,3-dimethyl-1-butene, 1-pentene, 1-pentene with one or more methyl, ethyl or propyl substituents, 1-hexene with one or more methyl, ethyl or propyl substituents, 1-heptene with one or more methyl, ethyl or propyl substituents, 1-octene with one or more methyl, ethyl or propyl substituents, 1-nonene with one or more methyl, ethyl or propyl substituents, ethyl, methyl or dimethyl substituted 1-decene, 1-dodecene, and styrene. The propylene content of such copolymers may be from about 60 mol% to about 99 mol%, in some embodiments from about 80 mol% to about 98.5 mol%, and in some embodiments from about 87 mol% to about 97.5 mol%. The α-olefin content may similarly range from about 1 mol % to about 40 mol %, in some embodiments from about 1.5 mol % to about 15 mol %, and in some embodiments, from about 2.5 mol % to about 13 mol %.

[0039]

[0041] Suitable propylene polymers typically have a DTUL value, as determined according to ISO 75:2013 at a load of 1.8 MPa, of about 80° C. to about 250° C., in some embodiments, about 100° C. to about 220° C., and in some embodiments, about 110° C. to about 200° C. The glass transition temperature of such polymers may also be about 10° C. to about 80° C., in some embodiments, about 15° C. to about 70° C., and in some embodiments, about 20° C. to about 60° C. Additionally, the melting temperature of such polymers may be about 50° C. to about 250° C., in some embodiments, about 90° C. to about 220° C., and in some embodiments, about 100° C. to about 200° C.

[0040]

[0042] Oxymethylene polymers may also be suitable aliphatic high performance polymers for use in the polymer matrix. The oxymethylene polymer may be one or more homopolymers, copolymers, or mixtures thereof. Homopolymers are prepared by polymerizing formaldehyde or formaldehyde equivalents, such as cyclic oligomers of formaldehyde. Copolymers may contain one or more comonomers commonly used to prepare polyoxymethylene compositions. Commonly used comonomers include alkylene oxides of 2-12 carbon atoms. If a copolymer is selected, the amount of comonomer is usually 20 weight percent or less, in some embodiments 15 weight percent or less, and in some embodiments about 2 weight percent. Comonomers may include ethylene oxide and butylene oxide. It is preferred that homopolymers and copolymers are 1) end-capped by chemical reaction in which the terminal hydroxyl groups form ester or ether groups; or 2) copolymers that are not fully end-capped but have some free hydroxyl ends from the comonomer units. Typical end groups in both cases are acetate and methoxy.

[0041] B. Carbon Nanostructures

[0043] As noted above, the carbon nanostructures are also distributed within the polymer matrix. The carbon nanostructures are typically used in an amount of about 0.1 parts by weight to about 10 parts by weight, in some embodiments about 0.2 parts by weight to about 6 parts by weight, and in some embodiments about 0.5 parts by weight to about 2.5 parts by weight per 100 parts by weight of the polymer matrix. For example, the carbon nanostructures may comprise about 0.1% by weight to about 5% by weight, in some embodiments about 0.2% by weight to about 3% by weight, and in some embodiments about 0.4% by weight to about 1.5% by weight of the polymer composition. The polymer matrix may, in some embodiments, comprise about 1% by weight to about 90% by weight, in some embodiments about 5% by weight to about 80% by weight, in some embodiments about 10% by weight to about 70% by weight, in some embodiments about 20% by weight to about 60% by weight, and in some embodiments about 30% by weight to about 50% by weight of the polymer composition.

[0042]

[0044] Carbon nanostructures generally include carbon nanotubes, which may be optionally disposed on a substrate, and are arranged in a network having a mesh-like morphology, with at least a portion of the carbon nanotubes being branched, cross-linked, interdigitated, sharing a common wall with one another, etc. It should be understood that not all carbon nanotubes necessarily have the aforementioned structural characteristics. Rather, the carbon nanotubes as a whole can have one or more of these structural characteristics. For example, in some embodiments, some of the carbon nanotubes may be branched, another portion of the carbon nanotubes may be cross-linked, but still another portion of the carbon nanotubes may share a common wall. Similarly, in some embodiments, at least a portion of the carbon nanotubes may be interdigitated with each other and / or with the branched, cross-linked, or common-walled carbon nanotubes in the remainder of the carbon nanostructure. FIGS. 1A-1C show illustrative depictions of carbon nanotubes 1-3, which are branched, cross-linked, and share a common wall, respectively.

[0043]

[0045] The network-like morphology of carbon nanostructures can result in low bulk density. For example, as-produced carbon nanostructures have a bulk density of about 0.003 g / cm 3 ~Approx. 0.015g / cm 3 With further densification and / or coating to produce a flake material or similar morphology, the initial bulk density can range between about 0.1 g / cm 3 ~Approx. 0.15g / cm 3 In some embodiments, optional further modification of the carbon nanostructures can be performed to further alter the bulk density and / or other properties of the carbon nanostructures. In some embodiments, the bulk density of the carbon nanostructures can be further altered by coating the carbon nanotubes and / or infiltrating the interior of the carbon nanostructures with various materials. Coating the carbon nanotubes and / or infiltrating the interior of the carbon nanostructures can further tailor the properties of the carbon nanostructures for use in various applications. Furthermore, in some embodiments, coating the carbon nanotubes can desirably facilitate easier handling of the carbon nanostructures. Further compaction can be achieved up to about 1 g / cm. 3 The bulk density was increased to the upper limit of 1.2 g / cm by chemical modification of carbon nanostructures. 3 The bulk density can be increased to the upper limit.

[0044]

[0046] Various techniques may be used to form carbon nanostructures. In one embodiment, for example, carbon nanotubes may be formed (e.g., grown, infused, etc.) on a substrate. Depending on the desired morphology of the nanostructures, the carbon nanotubes may be detached from the substrate or may remain on it. Examples of techniques for growing nanotubes on a substrate are described, for example, in U.S. Patent No. 2014 / 0093728, as well as U.S. Patent Nos. 8,784,937; 9,005,755; 9,107,292; 9,241,433; and 9,447,259, all of which are incorporated herein by reference in their entirety. Without being limited by theory, it is believed that the use of a substrate may aid in the formation of complex, network-like morphologies due to the ability of carbon nanotubes to grow at rapid rates, such as on the order of several micrometers per second. The rapid carbon nanotube growth rates may allow nearby carbon nanotubes to link together, imparting the observed branched, bridged, and shared wall motifs to the carbon nanotubes.

[0045]

[0047] Any of a variety of substrates may be used during the synthesis of carbon nanostructures, such as glass, inorganic materials, carbon materials, metals, polymers, etc. In some embodiments, the substrate may be a fibrous material (e.g., fabric, tow, fiber, yarn, sheet, tape, belt, etc.) of dimensions that allow it to be wound onto a spool, thereby allowing the formation of carbon nanotubes to occur continuously on the substrate as it is transported from a first location to a second location. Such fibrous materials may also provide additional functional benefits to the polymer composition, such as improved strength and / or enhanced electrical conductivity, if they sustain bonding to the carbon nanotube structures. As used herein, the term "spoolable dimensions" generally refers to a fibrous material having at least one dimension that is not limited to length, allowing the material to be stored on a spool or mandrel. Suitable fiber materials include, for example, materials made from glass (e.g., E-glass, S-glass, D-glass, etc.), carbon (e.g., graphite), ceramics, polymeric materials (e.g., polyamide, aramid, polyester, etc.), metals (e.g., steel, aluminum, copper, tungsten, etc.), carbides (e.g., silicon carbide), cellulosic materials, etc., as well as combinations thereof. Carbon fiber materials are suitable, for example, particularly when it is desirable to further increase the electrical conductivity of the polymeric composition. When such fibers are used as substrates, carbon nanotubes may be infused into the fibers. For example, carbon nanotubes may generally grow vertically from the outer surface of the fiber, thereby providing a radial coating to the individual fibers. Carbon nanotubes may be grown in situ on the fibers. For example, the fibers may be fed through a growth chamber maintained at a given temperature of about 500° C. to about 750° C. A carbon-containing feed gas may then be introduced into the growth chamber, and carbon radicals dissociate and initiate the formation of carbon nanotubes in the fibers.

[0046]

[0048] Regardless of the nature of the substrate, a catalyst is typically used to help ensure the formation of the carbon nanostructures. Particularly suitable catalysts include, for example, transition metal nanoparticles. Suitable transition metal nanoparticle catalysts can include any d-block transition metal or d-block transition metal salt. Non-limiting exemplary transition metal nanoparticles may include nickel, iron, cobalt, molybdenum, copper, platinum, gold, silver, and the like, as well as salts and mixtures thereof. One manner for applying the catalyst to the substrate (e.g., injection) may be by particle adsorption, for example, by a solution of liquid or colloidal catalyst. For example, a catalyst solution containing nanoparticles including transition metals or their salts, such as acetates, carbides, and the like, may be used. In such embodiments, the transition metal salts can be converted to zero-valent transition metals on the substrate by heat treatment. The transition metal nanoparticles may also be coated with an anti-adhesive coating that limits their adhesion to the substrate, facilitating the removal of the carbon nanostructures from the substrate following the synthesis of the carbon nanostructures. In some embodiments, the carbon nanostructures can be removed from the substrate without substantially removing the transition metal nanoparticle catalyst.

[0047]

[0049] As noted above, the carbon nanotube structures may be optionally removed from the substrate. In such embodiments, known techniques may be used to remove the carbon nanotubes, such as providing an anti-adhesion coating to the substrate, providing an anti-adhesion coating to the transition metal nanoparticle catalyst used to synthesize the carbon nanostructures, providing the transition metal nanoparticle catalyst with a counterion that etches the substrate, thereby weakening the adhesion of the carbon nanostructures to the substrate, and / or performing an etching operation to weaken the adhesion of the carbon nanostructures to the substrate after the carbon nanostructure synthesis is completed. In one embodiment, for example, a high pressure liquid or gas may be used to separate the carbon nanostructures from the substrate. Thereafter, contaminants originating from the substrate (e.g., the fragmented substrate) may be separated from the carbon nanostructures, for example, by use of cyclone filtration, gravity separation, size-based separation, etc. The nanostructures may then be collected from the liquid medium using air or with the aid of a filter agent and subsequently isolated from the filter agent. Of course, in other embodiments, the carbon nanostructures are not removed from the substrate. This may be particularly desirable if the substrate itself can provide other functional benefits to the polymer composition.

[0048]

[0050] In some embodiments, at least some of the carbon nanotubes may be aligned substantially parallel to each other in the carbon nanostructure. Without being bound by any theory, it is believed that the formation of carbon nanotubes on a substrate under the carbon nanostructure growth conditions described herein results in the growth of at least the majority of the carbon nanotubes substantially perpendicular to the substrate surface. The substantially parallel alignment of the carbon nanotubes can be maintained even after optional removal of the carbon nanostructures from the substrate. In fact, the branching, bridging, and shared structural features of the carbon nanotube walls may become more prevalent at the location of the carbon nanotube that is further removed from the substrate. Nevertheless, because the carbon nanostructures can be obtained with the carbon nanotubes aligned substantially parallel to each other, they can be more easily manipulated in terms of alignment than individual carbon nanotubes, which may require further processing to induce the carbon nanotubes into a parallel alignment. The parallel alignment of the carbon nanotubes can improve electrical conductivity and increase mechanical strength in the direction of the alignment of the carbon nanotubes.

[0049]

[0051] The coating may also be applied to the carbon nanotubes of the carbon nanostructures before or after removal of the carbon nanostructures from the substrate. Application of the coating before removal of the carbon nanostructures from the substrate can, for example, protect the carbon nanotubes during or facilitate the removal process. In other embodiments, the coating can be applied to the carbon nanotubes of the carbon nanostructures after removal of the carbon nanostructures from the substrate. Application of the coating to the carbon nanotubes of the carbon nanostructures after their removal from the substrate can desirably facilitate handling and storage of the carbon nanostructures. In particular, the coating of the carbon nanostructures can desirably facilitate densification or densification of the carbon nanostructures. Higher density can desirably facilitate processability of the carbon nanostructures. The coating can be covalently bonded to the carbon nanotubes of the carbon nanostructures. In some embodiments, the carbon nanotubes can be functionalized to provide suitable reactive functional groups for the formation of such coatings before or after removal of the carbon nanostructures from the substrate. Processes suitable for functionalizing the carbon nanotubes of the carbon nanostructures are generally similar to those that can be used to functionalize individual carbon nanotubes and are known to those skilled in the art. In other embodiments, the coating may be non-covalently attached to the carbon nanotubes of the carbon nanostructures, i.e., in such embodiments, the coating may be physically disposed on the carbon nanotubes.

[0050]

[0052] If desired, the coating on the carbon nanotubes may be a polymer coating. Suitable polymer coatings are not believed to be particularly limited and may include, for example, polymers such as epoxies, polyesters, vinyl ester polymers, polyetherimides, polyetherketoneketones, polyphthalamides, polyetherketones, polyetheretherketones, polyimides, phenol-formaldehyde polymers, bismaleimide polymers, acrylonitrile-butadiene styrene (ABS) polymers, polycarbonates, polyethyleneimines, polyurethanes, polyvinyl chloride, polystyrenes, polyolefins, polypropylenes, polyethylenes, polytetrafluoroethylenes, and any combinations thereof. In addition to polymer coatings, other types of coatings such as metal coatings and ceramic coatings may also be present. Another additive material may also be present at least in the interstitial spaces between the carbon nanotubes of the carbon nanostructures (i.e., within the carbon nanostructures). The additive material may be used alone or in combination with a coating on the carbon nanotubes of the carbon nanostructures. The additive material may also be located on the outside of the carbon nanostructures within the coating in addition to being located within the interstitial spaces of the carbon nanostructures when used in combination with a coating. Introducing additive materials into the interstitial spaces of the carbon nanostructures or elsewhere within the carbon nanostructures can result in further modification of the properties of the carbon nanostructures. The nanostructures may also contain some transition metal nanoparticles that are used as catalysts during the synthesis of the nanostructures. The transition metal nanoparticles can be coated with an anti-adhesion coating that limits adhesion to the substrate or adhesion of the carbon nanostructures to the substrate. In various embodiments, the anti-adhesion coating can be carried along with the transition metal nanoparticles once the carbon nanostructures and transition metal nanoparticles are removed from the substrate. In other embodiments, the anti-adhesion coating can be removed from the transition metal nanoparticles before or after they are incorporated into the carbon nanostructures.In yet other embodiments, the transition metal nanoparticles can be first incorporated into the carbon nanostructures and then later removed. For example, in some embodiments, at least a portion of the transition metal nanoparticles can be removed from the carbon nanostructures by treating the carbon nanostructures with a mineral acid. The nanostructures may also contain a substrate.

[0051]

[0053] Carbon nanostructures may be provided in a variety of different forms, such as flakes, granules, pellets, fibers, or other forms of loosely dispersed particles. In some embodiments, it may be desirable to use carbon nanostructures in the form of flake material, which includes individual particles having finite dimensions. FIG. 2 shows an illustrative depiction of a carbon nanostructure flake material. The flake structure 100 can have a first dimension 110 ranging from about 1 nm to about 35 μm in thickness, in particular from about 1 nm to about 500 nm in thickness, inclusive of all values ​​and fractions therebetween. The flake structure 100 can have a second dimension 120 ranging from about 1 micron to about 750 microns in height, inclusive of all values ​​and fractions therebetween. The flake structure 100 can have a third dimension 130 that is limited only in size based on the length of the substrate on which the carbon nanostructures were initially formed. For example, in some embodiments, the process of growing carbon nanostructures on a substrate can be carried out on a tow or roving of a fibrous material of dimensions that allow it to be wound onto a spool. The carbon nanostructure growth process may be continuous, and the carbon nanostructures may extend the entire length of the spool of fiber. Thus, in some embodiments, the third dimension 130 may range from about 1 m to about 10,000 m wide. Again, the third dimension 130 may be very long since it corresponds to the dimension along the axis of the substrate on which the carbon nanostructures are formed. The third dimension 130 may also be reduced to any desired length less than 1 μm. For example, in some embodiments, the third dimension 130 may be on the order of about 1 μm to about 10 μm, or about 10 μm to about 100 μm, or about 100 μm to about 500 μm, or about 500 microns to about 1 cm, to any desired length, including all amounts and fractions thereof between the stated ranges. Because the substrate on which the carbon nanostructures are formed may be quite large, exceptionally high molecular weight carbon nanostructures may be produced by forming a polymer-like morphology of the carbon nanostructures as a continuous layer on a suitable substrate.

[0052]

[0054] Still referring to FIG. 2, the flake structure 100 can include a mesh-like network of carbon nanotubes 140 in the form of carbon nanotube polymers (i.e., "carbon nanopolymers") having a molecular weight ranging from about 15,000 g / mol to about 150,000 g / mol, including all values ​​and fractions therebetween. In some embodiments, the upper end of the molecular weight range can be even higher and include about 200,000 g / mol, about 500,000 g / mol, or about 1,000,000 g / mol. High molecular weight can be associated with dimensionally long carbon nanostructures. In various embodiments, the molecular weight can also be a function of the primary carbon nanotube diameter and the number of carbon nanotube walls present within the carbon nanostructure. In some embodiments, the carbon nanostructures can have a molecular weight of about 2 mol / cm. 3 ~about 80mol / cm 3 The crosslink density can range between 0.01 to 0.05, and the crosslink density can be a function of the carbon nanostructure growth density on the substrate surface as well as the carbon nanostructure growth conditions.

[0053]

[0055] FIG. 3 shows an SEM image of an illustrative carbon nanostructure obtained as a flake material. The carbon nanostructure shown in FIG. 3 exists as a three-dimensional microstructure due to the entanglement and cross-linking of its highly aligned carbon nanotubes. The aligned morphology reflects the formation of carbon nanotubes on the substrate under rapid carbon nanotube growth conditions (e.g., several microns per second, e.g., about 2 microns per second to about 10 microns per second), thereby inducing the growth of carbon nanotubes substantially perpendicular from the substrate. Without being bound by theory, it is believed that the rapid rate of carbon nanotube growth on the substrate may contribute, at least in part, to the complex network-like morphology of the carbon nanostructures. Furthermore, the bulk density of the carbon nanostructures may be tuned to some extent by adjustment of the carbon nanostructure growth conditions, including, for example, varying the concentration of transition metal nanoparticle catalyst particles disposed on the substrate to initiate carbon nanotube growth. The desired flake material may desirably be obtained after isolation of the carbon nanostructures from the substrate, as described above.

[0054]

[0056] As used herein, a "carbon nanotube" as used in nanostructures is any number of cylindrically shaped carbon allotropes of the fullerene group, including single-walled carbon nanotubes (SWNTs), double-walled carbon nanotubes (DWNTs), multi-walled carbon nanotubes (MWNTs), and the like, as well as combinations thereof. Carbon nanotubes can be closed by fullerene-like structures, or can be open-ended and contain encapsulated other materials. SWCNTs can be considered as sp2 hybridized carbon allotropes similar to fullerenes. The structure is a cylindrical tube containing six-membered carbon rings. On the other hand, the analogous MWCNTs have several tubes in a concentric cylinder. The number of these concentric walls can vary, such as from 2 to 25 or more. Typically, the diameter of MWNTs can be 10 nm or more, compared to 0.7 to 2.0 nm for typical SWNTs. Carbon nanostructures used in polymer compositions are typically desirably formed from MWCNTs, such as those having at least two coaxial carbon nanotubes. The number of walls present, as determined, for example, by transmission electron microscopy (TEM) at a magnification sufficient to analyze the number of walls in a particular case, may be in the range of 2 to 30, in some embodiments 4 to 28, in some embodiments 5 to 26, and in some embodiments 6 to 24. Carbon nanotubes present in or derived from carbon nanostructures usually have a typical diameter of 100 nanometers or less, in some embodiments about 5 to about 90 nanometers, and in some embodiments about 10 to about 30 nanometers. Carbon nanotubes may also have a length of about 2 micrometers or more, in some embodiments about 2 to about 10 micrometers, and in some embodiments about 2.5 to about 5 micrometers. The aspect ratio of carbon nanotubes may also be relatively high, for example about 200 to about 1,000, in some embodiments about 300 to about 900, and in some embodiments about 400 to about 800.

[0055] C. Other ingredients

[0057] As discussed above, carbon nanostructures may be formed on a substrate that includes a fibrous material, such as glass fiber, carbon fiber, and the like. In some embodiments, such carbon nanostructures may contain the only fibrous material in the polymer composition, or at a minimum, a significant portion of the fibrous material in the composition, such as greater than about 50% by weight, and in some embodiments, greater than about 75% by weight, of the fibrous material in the composition. Thus, for example, the polymer composition may generally be free of additional reinforcing fibers. Nonetheless, in some cases, additional fibers may also be used, but in relatively small amounts. For example, when used, the additional reinforcing fibers typically comprise no more than about 40% by weight of the composition, no more than about 30% by weight of the composition, and in some embodiments, from about 1% to about 25% by weight of the composition. Such reinforcing fibers may also generally be formed from essentially insulating materials, such as glass, ceramics (e.g., alumina or silica), aramids (e.g., Kevlar®), polyolefins, polyesters, and the like, as well as mixtures thereof. Glass fibers, such as E-glass, A-glass, C-glass, D-glass, AR-glass, R-glass, S1-glass, S2-glass, and the like, and mixtures thereof, are particularly suitable. The reinforcing fibers may be in the form of randomly distributed fibers, for example, when such fibers are melt blended with the high performance polymer(s) during the formation of the polymer matrix. Regardless, the volume average length of the reinforcing fibers may be from about 1 to about 400 micrometers, in some embodiments from about 50 to about 400 micrometers, in some embodiments from about 80 to about 250 micrometers, in some embodiments from about 100 to about 200 micrometers, and in some embodiments from about 110 to about 180 micrometers. The fibers may also have an average diameter of from about 10 to about 35 micrometers, and in some embodiments from about 15 to about 30 micrometers.

[0056]

[0058] As noted above, carbon nanostructures also contain electrically conductive carbon nanotubes that may be optionally formed (e.g., implanted) on a substrate that may itself be electrically conductive (e.g., carbon fiber). In some embodiments, such carbon nanostructures may comprise the only electrically conductive material in the polymer composition, or at the very least, a significant portion of the electrically conductive material in the composition, e.g., greater than about 50% by weight, and in some embodiments, greater than about 75% by weight, of the electrically conductive material in the composition. Thus, for example, the polymer composition may generally be free of additional electrically conductive material. Nevertheless, in some cases, additional electrically conductive material may still be used, but in relatively small amounts. For example, the electrical conductivity may be less than about 1 Ω·cm, in some embodiments less than about 0.1 Ω·cm, and in some embodiments, less than about 1×10, as determined at a temperature of about 20° C. -8 ~Approx. 1×10 -2 Additional electrically conductive carbon materials having a volume resistivity of Ω·cm may be used. Suitable electrically conductive carbon materials may include, for example, graphite, carbon black, carbon fibers, graphene, other types of carbon nanotubes, and the like. Other suitable electrically conductive fillers may also include metals (e.g., metal particles, metal flakes, metal fibers, nanodiamonds, carbon black, and the like), ionic liquids, and the like. When used, for example, the electrically conductive fillers may comprise from about 0.1% to about 10% by weight, in some embodiments from about 0.2% to about 8% by weight, and in some embodiments, from about 0.5% to about 6% by weight of the polymer composition.

[0057]

[0059] In some embodiments, it may also be desirable to use a dielectric filler in the polymer composition. When used, the dielectric filler is typically present in an amount of about 10% to about 60% by weight of the composition, in some embodiments about 20% to about 55% by weight, and in some embodiments about 30% to about 50% by weight. In some embodiments, it may be desirable to selectively control the electrical properties of the dielectric filler to help achieve the desired results. For example, the dielectric constant of the material may be about 20 or more, in some embodiments about 40 or more, and in some embodiments about 50 or more, measured at a frequency of 1 MHz. In some embodiments, high dielectric constant materials may be used, for example, about 1,000 to about 15,000, in some embodiments about 3,500 to about 12,000, and in some embodiments about 5,000 to about 10,000, measured at a frequency of 1 MHz. In other embodiments, medium dielectric constant materials may be used, for example, about 20 to about 200, in some embodiments about 40 to about 150, and in some embodiments about 50 to about 100, measured at a frequency of 1 MHz. The volume resistivity of the dielectric filler may also be, for example, about 1×10 as determined at a temperature of about 20° C. according to ASTM D257-14. 11 ~Approx. 1×10 20 Ω cm, in some embodiments, about 1×10 12 ~Approx. 1×10 19 Ω cm, in some embodiments, about 1×10 13 ~Approx. 1×10 18 The desired properties may be achieved by selecting a single material with the target volume dielectric constant and / or volume resistivity, or by blending multiple materials together such that the resulting blend has the desired properties (e.g., insulating and electrically conductive).

[0058]

[0060] Particularly suitable inorganic oxide materials may include, for example, ferroelectric and / or paraelectric materials. Examples of suitable ferroelectric materials are, for example, barium titanate (BaTiO3), strontium titanate (SrTiO3), calcium titanate (CaTiO3), magnesium titanate (MgTiO3), barium strontium titanate (SrBaTiO3), sodium barium niobate (NaBa2Nb5O3), and the like. 15 ), potassium barium niobate (KBa2Nb5O 15 ), calcium zirconate (CaZrO3), titanite (CaTiSiO5), and combinations thereof. Examples of suitable paraelectric materials also include, for example, titanium dioxide (TiO2), tantalum pentoxide (Ta2O5), hafnium dioxide (HfO2), niobium pentoxide (Nb2O5), alumina (Al2O3), zinc oxide (ZnO), and the like, and combinations thereof. Particularly suitable inorganic oxide raw materials are particles including TiO2, BaTiO3, SrTiO3, CaTiO3, MgTiO3, BaSrTi2O6, and ZnO. Of course, other types of inorganic oxide materials (e.g., mica) may also be used as the dielectric filler.

[0059]

[0061] In one particular embodiment, titanium dioxide (TiO2) particles may be used in the polymer composition as a dielectric filler. The particles may be in rutile or anatase crystalline form, with rutile being particularly suitable due to its high density and color intensity. Rutile titanium dioxide is usually produced by either the chloride or sulfate process. In the chloride process, TiCl4 is oxidized to TiO2 particles. In the sulfate process, sulfuric acid and titanium-containing ores are dissolved, and the resulting solution undergoes a series of steps to produce TiO2. Preferably, the titanium dioxide particles are in rutile crystalline form and may be produced using the chloride process. The titanium dioxide particles may be substantially pure titanium dioxide or may contain other metal oxides, such as, for example, silica, alumina, zirconia, etc. Other metal oxides may be incorporated into the particles by co-oxidizing or co-precipitating the titanium compound with other metal compounds, such as, for example, metal halides of silicon, aluminum, and zirconium. When co-oxidized or coprecipitated metals are present, they are typically present as metal oxides in an amount of 0.1 to 5 weight percent based on the weight of the titanium dioxide particles. When alumina is incorporated into the particles by co-oxidation of an aluminum halide (e.g., aluminum chloride), the alumina is typically present in an amount of about 0.5 to about 5 weight percent, and in some embodiments, about 0.5 to about 1.5 weight percent, based on the total weight of the particles. The titanium dioxide particles may also be coated with inorganic oxides (e.g., alumina), organic compounds, or combinations thereof. Such coatings may be applied using surface wet treatment techniques and / or oxidation techniques known to those skilled in the art. In one embodiment, for example, the titanium dioxide particles may contain a coating comprising alumina in an amount of, for example, about 0.5 to about 5 weight percent, and in some embodiments, about 1 to about 3 weight percent of the coating.

[0060]

[0062] The shape and size of the dielectric filler are not particularly limited and may include particles, fine powders, fibers, whiskers, tetrapods, plates, etc. In one embodiment, for example, the dielectric filler may include particles having an average diameter of about 0.01 to about 50 micrometers, in some embodiments, about 0.05 to about 10 micrometers, and in some embodiments, about 0.1 to about 1 micrometer.

[0061]

[0063] Another suitable dielectric filler may include polyhedral silsesquioxanes ("POSS"). Polyhedral silsesquioxanes have the general formula (RSiO 1.5 ) n where R is an organic moiety and n is 6, 8, 10, or 12 or more. These molecules have a rigid, thermally stable silicon-oxygen backbone with an oxygen to silicon ratio of 1.5. A specific example of the Si8POSS structure is illustrated below:

[0062] [ka]

[0063]

[0064] Functionalized POSS monomers may also be used, for example, by corner-capping an incompletely condensed POSS containing a trisilanol group with a substituted trichlorosilane. For example, the trisilanol functionality of R7T4D3(OH)3, where R is a hydrocarbon group, can be reacted with Cl3Si-Y to produce a fully condensed POSS monomer R7T8Y. In the following structure, T is SiO 1.5 and Y is an organic group containing a functional group:

[0064] [ka]

[0065]

[0065] By modification of the Y group on the silane, a variety of functional groups can be placed away from the corners of the POSS backbone, including, but not limited to, halides, alcohols, amines, hydrides, isocyanates, acids, acid chlorides, silanols, silanes, acrylates, methacrylates, olefins, and epoxides.

[0066] Further examples of suitable POSS monomers have the general formula R n-m T n Y m [wherein R is a hydrocarbon; n is 6, 8, 10, 12 or more; m is 1 to n; T is SiO 1.5 and Y is an organic group containing a functional group. The functional groups include, for example, halides, alcohols, amines, isocyanates, acids, acid chlorides, silanols, silanes, acrylates, methacrylates, olefins, and epoxides. Suitable POSS monomers include, for example, n of 8; m of 1, 2, 3, 4, 5, 6, 7, or 8; C1-C 24 Linear, branched or cyclic alkyl, C1-C 24 and R includes aromatic, alkylaryl, or arylalkyl, where the alkyl or aromatic is optionally substituted with C-C alkyl, halo, C-C alkoxy, C-C perhaloalkyl, etc. Another suitable POSS monomer includes those of the general formula R7T4D3(OY)3:

[0067] [ka]

[0068]

[0067] where R and Y are as defined above for the R7T8Y POSS monomer. Suitable functional groups are epoxy, ester and acrylate (-X-OC(O)CH=CH2) and methacrylate (-X-OC(O)CH(CH3)=CH2) groups, where X is a divalent linking group having from 1 to about 36 carbons, such as methylene, ethylene, propylene, isopropylene, butylene, isobutylene, phenylene, and the like, and X may also be substituted with functional groups such as ethers (e.g., --CH2CH2OCH2CH2-), so long as such functional groups do not interfere with the formation or use of the POSS. X may be propylene, isobutylene, or --OSi(CH3)2CH2CH2CH2-. One, all, or an intermediate of the covalently linked groups may be an acrylate or methacrylate group (hereafter (meth)acrylate). The linking group X is suitable for use with other functional groups.Other POSS structures include alkoxysilanes such as diethoxymethylsilylethyl, diethoxymethylsilylpropyl, ethoxydimethylsilylethyl, ethoxydimethylsilylpropyl, and triethoxysilylethyl; styrenes such as styrenyl (-C6H5CH=CH-) and styryl (-C6H4CH=CH2); olefins such as allyl, -OSi(CH3)2CH2CH=CH2, cyclohexenylethyl, and -OSi(CH3)2CH=CH2; epoxies such as 4-propyl-1,2-epoxycyclohexyl, 3-propoxy, and glycidyl; chlorosilanes such as chlorosilylethyl, dichlorosilylethyl, and trichlorosilylethyl; amines such as aminopropyl and aminoethylaminopropyl; and -OSi(CH3)2CH2CH2CH2OC(CH2CH3)2(CH2CH with alcohols and phenols such as diphenylphosphinoethyl, diphenylphosphinopropyl; with norbornenyls such as norbornenylethyl; with nitriles such as cyanoethyl, cyanopropyl, -OSi(CH3)2CH2CH2CH2CN; with isocyanates such as isocyanatopropyl, -OSi(CH3)2CH2CH2CH2NCO; with halides such as 3-chloropropyl, chlorobenzyl (-C6H4CH2Cl), chlorobenzylethyl, 4-chlorophenyl, trifluoropropyl (including the T8 cube with 8 trifluoropropyl substitutions); and with esters such as ethylundecanoate-1-yl and methylpropionate-1-yl. 10 or T 12 Includes structure.

[0069]

[0069] Of course, various other optional components may also be employed in the polymer composition, such as thermally conductive fillers, impact modifiers, compatibilizers, particulate fillers (e.g., talc, mica, etc.), stabilizers (e.g., antioxidants, UV stabilizers, etc.), flame retardants, lubricants, dyes, flow control agents, pigments, and other materials added to enhance properties and processability. Suitable thermally conductive fillers may include, for example, carbon black, alumina, boron nitride, silica, carbon fiber, graphene, graphene oxide, graphite (e.g., expanded graphite, synthetic graphite, low-temperature expanded graphite, etc.), aluminum nitride, silicon nitride, metal oxides (e.g., zinc oxide, magnesium oxide, beryllium oxide, titanium oxide, zirconium oxide, yttrium oxide, etc.), nanodiamonds, carbon nanotubes, (which may be the same as or different from those listed above), calcium carbonate, talc, mica, wollastonite, clays (including exfoliated clays), metal powders (e.g., aluminum, copper, bronze, brass, etc.), or mixtures thereof. In some embodiments, for example, the thermally conductive filler may include carbon fiber.

[0070]

[0070] Flow modifiers may also be used to help achieve the desired melt viscosity of the composition, especially when a thermoplastic polymer having a high intrinsic viscosity (e.g., polyaryletherketone, liquid crystal polymer, etc.) is used. When used, such flow modifiers are typically present in an amount of about 0.05 to about 5 parts, in some embodiments about 0.1 to about 1 part, and in some embodiments about 0.2 to about 1 part by weight, per 100 parts by weight of the liquid crystal polymer(s). For example, the flow modifier may comprise about 0.01% to about 5% by weight, in some embodiments about 0.05% to about 3% by weight, and in some embodiments about 0.1% to about 1% by weight of the polymer composition.

[0071] If desired, the thermoplastic polymer(s) may be melt processed in the presence of a flow modifier to aid in achieving the desired low melt viscosity without sacrificing other properties of the composition. In such cases, the flow modifier may be a compound containing one or more functional groups (e.g., hydroxyl, carboxyl, etc.). In general, the term "functional" means that the compound contains at least one functional group (e.g., carboxyl, hydroxyl, etc.) or is capable of having such functionality in the presence of a solvent. As used herein, functional compounds may be mono-, di-, tri-, etc. functional. The total molecular weight of the compound is relatively low so that the compound can effectively serve as a flow modifier for the polymer composition. The compound typically has a molecular weight of about 2,000 grams per mole or less, in some embodiments about 25 to about 1,000 grams per mole, in some embodiments about 50 to about 500 grams per mole, and in some embodiments about 100 to about 400 grams per mole. In general, any of a variety of functional compounds may be used. In some embodiments, the general formula M(OH) s Metal hydroxide compounds having the formula: may be used, where s is an oxidation state (usually 1-3) and M is a metal, e.g., a transition metal, an alkali metal, an alkaline earth metal, or a main group metal. Without being limited by theory, it is believed that such compounds can effectively "lose" water under process conditions (e.g., elevated temperatures) and aid in melt viscosity reduction. Examples of suitable metal hydroxides may include copper(II) hydroxide (Cu(OH)2), potassium hydroxide (KOH), sodium hydroxide (NaOH), magnesium hydroxide (Mg(OH)2), calcium hydroxide (Ca(OH)2), aluminum hydroxide (Al(OH)3), and the like. Also suitable are metal alkoxide compounds capable of forming hydroxyl functional groups in the presence of a solvent such as water. Such compounds have the general formula M(OR) s where s is an oxidation state (usually 1-3), M is a metal, and R is an alkyl. An example of such a metal alkoxide is copper(II) ethoxide (Cu 2+ (CH3CH2O- )2), potassium ethoxide (K + (CH3CH2O - )), Sodium Ethoxide (Na + (CH3CH2O - )), Magnesium ethoxide (Mg 2+ (CH3CH2O - )2), Calcium ethoxide (Ca 2+ (CH3CH2O - )2) etc.; Aluminum ethoxide (Al 3+ (CH3CH2O - )3), and the like. In addition to metal hydroxides, metal salt hydrates, typically represented by the formula MA*xH20, where M is a metal cation, A is an anion, and x is 1-20, and in some embodiments, 2-10, may also be used. Specific examples of such hydrates may include, for example, CaCl2·H2O, ZnCl2·4H2O, CoCl2·6H2O, CaSO4·2H2O, MgSO4·7H2O, CuSO4·5H2O, Na2SO4·10H2O, Na2CO3·10H2O, Na2B4O7·10H2O, and Ba(OH)2·8H2O.

[0072] II. Formation Regardless of the raw materials used, the carbon nanostructures and other optional components may be melt processed or blended together with the thermoplastic polymer(s) in a composition. The components may be fed, separately or in combination, to an extruder that includes at least one screw rotatably mounted and housed within a barrel (e.g., a cylindrical barrel) and may define a feed section and a melt section located downstream from the feed section along the length of the screw. The extruder may be a single screw or a twin screw extruder. The speed of the screw may be selected to achieve the desired residence time, shear rate, melt processing temperature, and the like. For example, the screw speed may range from about 50 to about 800 revolutions per minute ("rpm"), in some embodiments from about 70 to about 150 rpm, and in some embodiments from about 80 to about 120 rpm. The apparent shear rate during melt blending may also be about 100 s-1 ~about 10,000 seconds -1 , in some embodiments, about 500 seconds -1 ~about 5000 seconds -1 , in some embodiments, about 800 seconds -1 ~about 1200 seconds -1 The apparent shear rate may be in the range of 4Q / πR 3 where Q is the volumetric flow rate of the polymer melt (m 3 / s") and R is the radius ("m") of the capillary (e.g., extrusion die) through which the molten polymer flows.

[0073] III. Parts As indicated above, the polymer composition may be used in a wide variety of components of electronic devices. Such components may be formed using a variety of different techniques. Suitable techniques may include, for example, injection molding, low pressure injection molding, extrusion compression molding, gas injection molding, foam injection molding, low pressure gas injection molding, low pressure foam injection molding, gas extrusion compression molding, foam extrusion compression molding, extrusion molding, foam extrusion molding, compression molding, foam compression molding, gas compression molding, and the like. For example, an injection molding system may be used that includes a mold into which the polymer composition can be injected. The time in the injector can be controlled and optimized so that the polymer matrix does not solidify first. When the cycle time is reached and the barrel is full to discharge, a piston can act to inject the composition into the mold cavity. Compression molding systems may also be used. Similar to injection molding, molding of the polymer composition into the desired article is also performed in a mold. The composition may be placed into a compression mold using any known technique, for example by being picked up by an automated robotic arm. The temperature of the mold may be maintained above the solidification temperature of the polymer matrix for a desired period of time to allow solidification. The molding may then be solidified by lowering it below its melting temperature. The resulting product may be demolded. The cycle time for each molding process may be adjusted to accommodate the polymer matrix, achieve sufficient bonding, and enhance overall process productivity.

[0074] IV. Electronic Devices The polymeric composition and parts formed therefrom may be used in a wide variety of electronic devices depending on the particular properties desired. In one embodiment, for example, the polymeric composition may be used in an electronic device to help provide EMI shielding. In one such embodiment, the electronic device may include a housing that houses one or more electronic components (e.g., a printed circuit board, an antenna element, a radio frequency sensing element, a sensor, a light sensing and / or transmitting element (e.g., fiber optics), a camera, a global positioning device, etc.). The housing may include, for example, a base including a sidewall extending from the base. A cover may be supported on the sidewall of the base to define an interior in which the electronic component(s) are housed and protected from the external environment. Regardless of the particular configuration of the device, the polymeric composition may be used to form all or a portion of the housing and / or cover. In one embodiment, for example, the polymeric composition may be used to form the base and sidewall of the housing. The cover may be formed from the polymeric composition or a different material. In this regard, traditional EMI metal shielding (e.g., aluminum plates) can be eliminated from the device design, thereby reducing the weight and overall cost of the device. Nevertheless, in certain other embodiments, such additional shielding may be used. For example, the cover may contain additional metal components (e.g., aluminum plates) in some cases.

[0075]

[0075] For example, referring to Figure 4, one particular embodiment of an electronic device 100 that may incorporate the polymer composition of the present invention is shown. The electronic device 100 includes a housing 102 including a sidewall 132 extending from a base 114. If desired, the housing 102 may also include a shroud 116 that may house an electrical connector (not shown). Regardless, a printed circuit board ("PCB") is housed within the device 100 and attached to the housing 102. Among other things, the circuit board 104 includes holes 122 that align with and receive the posts 110 located on the housing 102. The circuit board 104 has a first surface 118 on which is provided an electrical circuit 121 that enables radio frequency operation of the device 100. For example, the RF circuit 121 may include one or more antenna elements 120a and 120b. The circuit board 104 also has a second surface 119 opposite the first surface 118 and may optionally include other electrical components such as components (e.g., digital signal processors, semiconductor memory, input / output interface devices, etc.) that enable digital electronic operation of the device 100. Alternatively, such components may be provided on an additional printed circuit board. The electrical components may be encapsulated internally using a cover 108 disposed on the circuit board 104 and attached to the housing 102 (e.g., sidewalls) by known techniques such as welding, adhesives, etc. As indicated above, the polymer composition of the present invention may be used to form all or part of the cover 108 and / or the housing 102. As noted above, a conventional EMI shield (e.g., an aluminum plate) may be eliminated because it has EMI shielding effectiveness.

[0076]

[0076] The EMI shielded electronic device may be used in a wide variety of applications. For example, the electronic device may be used in an automobile (e.g., an electric vehicle). When used in an automobile application, for example, the electronic device may be used to sense the positioning of the vehicle relative to one or more three-dimensional objects. In this regard, the device may include radio frequency sensing components, light detection or optical components, cameras, antenna elements, etc., as well as combinations thereof. For example, the device may be a radio detection and ranging (radar) device, a light detection and ranging (lidar) device, a camera module, a global positioning module, etc., or may be an integrated device combining two or more of these components. Such a device may thus employ a housing that houses one or more types of electronic components (e.g., printed circuit boards, antenna elements, radio frequency sensing devices, sensors, light detection and / or transmitting elements (e.g., optical fibers), cameras, global positioning devices, etc.). In one embodiment, a lidar device may be formed that includes a fiber optic assembly for receiving and transmitting light pulses housed within a housing / cover assembly, for example, in a manner similar to the embodiment discussed above. Similarly, a radar device typically includes one or more printed circuit boards having dedicated electrical components for handling radio frequency (RF) radar signals, digital signal processing tasks, and the like.

[0077]

[0077] As indicated above, the polymer composition of the present invention may also be well suited for providing electrostatic discharge properties to components of devices such as camera modules. For example, a camera module typically includes a housing in which a lens module including one or more lenses is disposed. Referring to FIG. 5, for example, an embodiment of a camera module 100 including a lens module 120 included in a housing is shown, where the lens module 120 includes a lens barrel 121 coupled to a lens holder 123. The lens barrel 121 may have a hollow cylindrical shape such that one or more lenses for imaging an object can be accommodated therein in an optical axis direction 1. The lens barrel 121 may be inserted into a hollow cavity provided in the lens holder 123, which may also be generally cylindrical, and the lens barrel 121 and the lens holder 123 may be coupled to each other by fasteners (e.g., screws), adhesives, and the like. The lens module 120 including the lens barrel 121 may be movable in an optical axis direction 1 by an actuator assembly 150 (e.g., for autofocusing). For example, in the illustrated embodiment, the actuator assembly 150 may include a magnetic body 151 and a coil 153 configured to move the lens module 120 in the optical axis direction 1. The magnetic body 151 may be mounted on one side of the lens holder 123, and the coil 153 may be arranged to face the magnetic body 151. The coil 153 may be mounted on a substrate 155, which may in turn be mounted on the housing 130, such that the coil 153 faces the magnetic body 151. The actuator assembly 150 may include a driver 160 mounted on the substrate 155 and configured to output a signal (e.g., a current) for driving the actuator assembly 150 in response to a control input signal. The actuator assembly 150 may receive the signal and generate a driving force to move the lens module 120 in the optical axis direction 1. If desired, a stopper 140 may be mounted on the housing 130 to limit the distance of movement of the lens module 120 in the optical axis direction 1.Furthermore, the shield case 110 is connected to the housing 130 and encloses the outer surface of the housing 130, thereby blocking electromagnetic waves generated during operation of the camera module 100.

[0078]

[0078] The actuator assembly may also include a guide unit disposed between the housing and the lens module to help guide the movement of the lens module. Any of a variety of guide units known in the art may be used, such as spring(s), ball bearing(s), electrostatic force generator, water pressure generator, etc. For example, a spring may be used that generates a preload that acts on the lens module and guides it in the desired optical axis direction. Alternatively, as illustrated in the embodiment shown in FIG. 1, a ball bearing 170 may act as the guide unit of the actuator assembly 150. More specifically, the ball bearing 170 may be in contact with an outer surface of the lens holder 123 and an inner surface of the housing 130 to guide the movement of the lens module 120 in the optical axis direction 1. That is, the ball bearing 170 may be disposed between the lens holder 123 and the housing 130 and may guide the movement of the lens module 120 in the optical axis direction by rolling. For this purpose, any number of ball bearings 170 may be used, generally 2 or more, in some embodiments 3-20, in some embodiments 4-12, etc. The ball bearings 170 may be spaced apart or in contact with one another, and may be stacked in a direction perpendicular to the optical axis direction 1. The size of the ball bearings 170 may vary as known to one of ordinary skill in the art. For example, the ball bearings may have an average size (e.g., diameter) of about 800 micrometers or less, in some embodiments about 600 micrometers or less, in some embodiments about 400 micrometers or less, and in some embodiments about 50 to about 200 micrometers.

[0079]

[0079] The polymer composition of the present invention may be used in any of the various components of the camera module. Referring again to Figure 5, for example, the polymer composition may be used to form all or part of the actuator assembly 150 (e.g., magnetic body 151, ball bearing 170, etc.), the housing 130, the lens barrel 121, the lens holder 123, the substrate 155, the stopper 140, the shielding case 110, and / or other parts of the camera module. For example, it may be particularly desirable to use the composition in the magnetic body 151, the lens barrel 121, and / or the lens holder 123 to help minimize optical misalignment.

[0080]

[0080] The resulting camera module can be used in a wide variety of electronic devices known in the art, such as portable electronic devices (e.g., cell phones, portable computers, tablets, watches, etc.), computers, televisions, automotive parts, etc. In a particular embodiment, the polymer composition may be used in a camera module, such as those used in wireless communication devices (e.g., cellular phones). Referring to Figures 6-7, for example, an embodiment of an electronic device 2 (e.g., a phone) including a camera module 100 is shown. As shown, the lens of the camera module 100 can be exposed outside the electronic device 2 through an opening 2b for imaging external objects. The camera module 100 can also be electrically connected to an application integrated circuit 2c to perform control operations according to a user's selection.

[0081]

[0081] The present invention may be better understood with reference to the following examples. EXAMPLES

[0082] Test Method Surface / Volume Resistivity: Surface and volume resistivity values ​​are generally determined according to IEC 62631-3-2-2016 and IEC 62631-3-1-1:2016 (equivalent to ASTM D257-14), respectively. According to this procedure, a standard test specimen (e.g., a 1-meter cube) is placed between two electrodes. A voltage is applied for 60 seconds and the resistance is measured. Surface resistivity is the quotient of the potential gradient (V / m) and the current per unit electrode length (A / m), and generally represents the resistance to leakage current along the surface of an insulating material. Since the four ends of the electrodes define a square, the length in the quotient is reduced and the surface resistivity is reported in ohms, although the more descriptive unit of ohms / square is also commonly found. Volume resistivity is also determined as the ratio of the potential gradient parallel to the current in the material to the current density. In SI units, volume resistivity is numerically equal to the DC resistance (Ω·m) between opposing faces of a cubic metre of material.

[0083] Electromagnetic Interference ("EMI") Shielding: EMI shielding effectiveness may be determined in the frequency range of 700 MHz to 18 GHz (e.g., 5 GHz) according to ASTM-D4935-18. The thickness of the tested part may vary, for example, from 1 millimeter, 1.6 millimeters, or 3 millimeters. Testing may be performed using EM-2108 standard test equipment, which is an expanded section of coaxial transmission line and is available from various manufacturers such as Electro-Metrics. Measurement data relates to shielding effectiveness with plane waves (far-field EM waves), from which near-field values ​​for magnetic and electric fields may be inferred.

[0084] Tensile modulus, tensile stress and elongation at break: Tensile properties may be tested according to ISO527-1:2019 (technically equivalent to ASTM D638-14). Modulus and strength measurements may be performed on dog-bone shaped specimen samples with a length of 170 / 190 mm, a thickness of 4 mm and a width of 10 mm. Test temperatures may be -30°C, 23°C or 80°C and test speeds may be 1 or 5 mm / min.

[0085] Flexural modulus, elongation at break and flexural stress: Flexural properties may be tested according to ISO178:2019 (technically equivalent to ASTM-D790-17). The test may be performed at a support span of 64 mm. The test may be performed at the center section of an uncut ISO-3167 multipurpose bar. The test temperature may be -30°C, 23°C or 80°C, and the test speed may be 2 mm / min.

[0086] Charpy Impact Strength: Charpy properties may be tested according to ISO179-1:2010 (technically equivalent to ASTM-D6110). This test may be performed using a Type 1 specimen size (80 mm length, 10 mm width and 4 mm thickness). Specimens may be cut from the center section of the general purpose bar using a single tooth milling machine. Test temperatures may be -30°C, 23°C or 80°C.

[0087]

[0087] Deflection Temperature Under Load ("DTUL"): Deflection temperature under load may be determined according to ISO 75-2:2013 (technically equivalent to ASTM-D648-07). In particular, a test specimen sample having a length of 80 mm, width of 10 mm, and thickness of 4 mm may be subjected to a lateral three-point bend test with a prescribed load (maximum outer fiber stress) of 1.8 megapascals. The test specimen may be lowered into a silicone oil bath in which the temperature is increased at 2°C / min until it is deflected 0.25 mm (0.32 mm as per ISO Test No. 75-2:2013).

[0088] Melting Temperature: As known in the art, melting temperature ("Tm") may be determined by differential scanning calorimetry ("DSC"). Melting temperature is the Differential Scanning Calorimetry (DSC) peak melting temperature as determined by ISO 11357-2:2020. Under the DSC procedure, as specified in ISO Standard 10350, samples were heated and cooled at 20°C per minute using DSC measurements performed on a TA Q2000 Instrument.

[0089] Melt Viscosity: Melt viscosity (Pa·s) was measured over 1,000 s using a Dynisco LCR7001 capillary rheometer according to ISO Test No. 11443:2021. -1 and 15°C above the melt temperature. The rheometer orifice (die) had a diameter of 1 mm, a length of 20 mm, an L / D ratio of 20.1, and an entrance angle of 180°. The barrel diameter was 9.55 mm + 0.005 mm and the rod length was 233.4 mm.

[0090] Examples 1-4 Examples 1-4 are formed from various combinations of liquid crystal polymers (LCP1 and / or LCP2), glass fibers, aluminum hydroxide ("ATH"), titanium dioxide particles (chloride rutile with alumina and hydrophobic organic surface treatment, 0.27 μm average particle size), carbon fibers, and carbon nanostructures. LCP1 is formed from 43% HBA, 9% TA, 29% HQ, and 20% NDA. LCP2 is formed from 78% HBA and 27% HNA. Compounding was performed using a 32 mm single screw extruder. The components of each example are described in more detail below.

[0091] [Table 1]

[0092]

[0091] Examples 1-4 were tested for mechanical, thermal and electrical properties as described herein, with the results being set forth below.

[0093] [Table 2]

[0094]

[0092] These and other modifications and variations of the present invention can be implemented by those skilled in the art without departing from the spirit and scope of the present invention. Furthermore, it should be understood that aspects of the various embodiments can be interchanged in whole or in part. Furthermore, those skilled in the art will recognize that the above description is for illustrative purposes only and is not intended to limit the invention as further described in the appended claims.

Claims

1. 1. A polymeric composition comprising carbon nanostructures dispersed within a polymer matrix containing a thermoplastic polymer having a deflection temperature under load of about 40°C or greater and a melting temperature of about 140°C or greater, as determined according to ISO 75:2013 at a load of 1.8 MPa, said carbon nanostructures comprising carbon nanotubes arranged in a network having a mesh-like morphology, and optionally disposed on a substrate.

2. 10. The polymer composition of claim 1, having a viscosity of about 1×10 measured at a temperature of about 20° C. according to IEC 62631-3-2:2016 12 A polymeric composition exhibiting a surface resistivity of less than 1 Ohm.

3. 10. The polymer composition of claim 1, having a viscosity of about 1×10 measured at a temperature of about 20° C. according to IEC 62631-3-1:2016 7 A polymer composition exhibiting a volume resistivity of less than or equal to Ω·m.

4. 10. The polymer composition of claim 1, wherein the thermoplastic polymer has a deflection temperature under load of about 150°C or greater, determined according to ISO 75:2013 at 1.8 MPa.

5. The polymer composition of claim 1 , wherein the thermoplastic polymer comprises an aromatic polymer.

6. The polymer composition of claim 5 , wherein the aromatic polymer comprises a thermotropic liquid crystalline polymer.

7. 7. The polymer composition of claim 6, wherein the thermotropic liquid crystalline polymer contains repeat units derived from one or more aromatic dicarboxylic acids, one or more aromatic hydroxycarboxylic acids, or a combination thereof.

8. The polymer composition of claim 7, wherein the aromatic hydroxycarboxylic acid comprises 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, or a combination thereof.

9. The polymer composition of claim 7, wherein the aromatic dicarboxylic acid comprises terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, or a combination thereof.

10. 8. The polymer composition of claim 7, wherein the thermotropic liquid crystalline polymer further contains repeat units derived from one or more aromatic diols.

11. The polymer composition of claim 10, wherein the aromatic diol comprises hydroquinone, 4,4'-biphenol, or a combination thereof.

12. 8. The polymer composition of claim 7, wherein the thermotropic liquid crystalline polymer is wholly aromatic.

13. 8. The polymer composition of claim 7, wherein the thermotropic liquid crystal polymer comprises repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids in an amount of about 10 mol % or more.

14. The polymer composition of claim 1 , wherein the thermoplastic polymer comprises a polyarylene sulfide.

15. 10. The polymer composition of claim 1, wherein the thermoplastic polymer comprises a polyaryletherketone.

16. 10. The polymer composition of claim 1, wherein the carbon nanostructures are present in an amount of about 0.1 parts by weight to about 10 parts by weight per 100 parts by weight of the polymer matrix.

17. The polymer composition of claim 1 , wherein the carbon nanostructures are in the form of flake material.

18. 10. The polymer composition of claim 1, wherein the carbon nanostructures comprise a substrate, and the carbon nanotubes are infused onto the substrate.

19. 20. The polymer composition of claim 18, wherein the substrate comprises a fibrous material.

20. 20. The polymer composition of claim 19, wherein the fibrous material comprises carbon fiber, glass fiber, or a combination thereof.

21. The polymer composition of claim 1 , wherein the polymer composition contains an electrically conductive filler.

22. The polymer composition of claim 1 , wherein the polymer composition contains reinforcing fibers.

23. The polymer composition of claim 1 , wherein the polymer composition contains a dielectric filler.

24. 24. The polymer composition of claim 23, wherein the dielectric filler comprises a polyhedral silsesquioxane.

25. 13. An electronic device comprising a housing, at least one electronic component mounted in the housing, and a shield mounted over a first side of the electronic component, wherein the shield and / or housing comprises the polymer composition of claim 1.

26. 26. The electronic device of claim 25, wherein the electronic component comprises an antenna element.

27. 26. The electronic device of claim 25, wherein the electronic device is a radar device.

28. 30. The electronic device of claim 27, further comprising a radome mounted over the shield.

29. A camera module comprising a housing having disposed therein a lens module including one or more lenses, said camera module comprising the polymer composition of claim 1.

30. 30. The camera module of claim 29, wherein at least a portion of the housing, a lens module, or a combination thereof contains the polymer composition.

31. 30. The camera module of claim 29, wherein the lens module includes a lens barrel coupled to a lens holder.

32. 32. The camera module of claim 31, wherein at least a portion of the lens holder, the lens barrel, or a combination thereof contains the polymer composition.

33. 32. The camera module of claim 31, wherein the lens barrel houses the one or more lenses.